APPLICATION OF FUZZY FAULT TREE ANALYSIS FOR DETERMINATION OF RAILWAY CROSSING RELIABILITY - Tričković, Goran; Milosavljević, Milan; Bundalo, Zoran; Bursać, Marko (Horizons - International Scientific Journal, 2018)
Fault tree analysis (FTA) is one of the basic and most used methods for safety and reliability analysis of technical systems. This method is especially suitable for analysis system, which failures can cause serious consequences that affect on human lives and environment. Railway crossings, as places of crossroads of road and rail traffic, constitute one of the most important sources of potential conflicts and accidents in the railroad domain. The probability of occurrence of an unwanted event is increased if the participants in the traffic do not respect the rules or if a malfunction has occurred on the technical device of the railway crossing. In this paper FTA model was created in combination with fuzzy logic. Fuzzy logic in this model is used to represent imprecisely probabilities of failure of the system. By using the technique we proposed herein, values are transformed into the fuzzy numbers to give a realistic estimate of failure possibility of a basic event in FTA. The aim of this paper was to form a model which can identify scenarios and events that have the most affect on unwanted top event. This can lead to reduce number of accidents on railway crossing.Model was tested for one railway crossing in Pirot for basic top event “Passing the train by the unsecured railway crossing”. Final ranking on events by their impact on failure of system was done through fuzzy importance index.